2006
DOI: 10.1002/jcb.21143
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatments with the low‐calcemic 1,25(OH)2D3 analogs JKF or QW increase both the morphological and biochemical responses to estradiol‐17β in rat tibiae

Abstract: We demonstrated previously that daily injection for 3 days of the less calcemic vitamin D analogs: JK 1624 F(2)-2 (JKF) and QW 1624F(2)-2 (QW) followed by estradiol-17beta (E(2)) in female rats upregulated creatine kinase-specific activity (CK) in skeletal tissues. In this study, we evaluated both histomorphological and biochemical changes due to a regime of 4 days treatment with JKF or QW, followed by injection of E(2) on day 5, repeated for 2.5 months. Ovariectomized female rats (Ovx) were injected 2 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In the present study, we compared the effects of long‐term daily treatment with E 2 , the SERM Ral or isolated phytoestrogens and their synthetic carboxy‐derivatives or vehicle on bone histology regarding their ability to prevent damage to bones caused by Ovx, leading to decreased trabecular mass and increased adipogenesis in bone marrow, as well as on a biochemical marker the CK specific activity in skeletal tissues of female rats. Ovariectomy caused almost a complete cessation of bone growth as demonstrated in the disruption of the growth plate cell organization, and the complete disappearance of thin bone spicules, as previously reported [Somjen et al, 2007]. The increased number of adipocytes in the bone marrow adjacent to the growth plate indicated that this treatment might affect the overall metabolism of bone marrow.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, we compared the effects of long‐term daily treatment with E 2 , the SERM Ral or isolated phytoestrogens and their synthetic carboxy‐derivatives or vehicle on bone histology regarding their ability to prevent damage to bones caused by Ovx, leading to decreased trabecular mass and increased adipogenesis in bone marrow, as well as on a biochemical marker the CK specific activity in skeletal tissues of female rats. Ovariectomy caused almost a complete cessation of bone growth as demonstrated in the disruption of the growth plate cell organization, and the complete disappearance of thin bone spicules, as previously reported [Somjen et al, 2007]. The increased number of adipocytes in the bone marrow adjacent to the growth plate indicated that this treatment might affect the overall metabolism of bone marrow.…”
Section: Discussionsupporting
confidence: 77%